2019
DOI: 10.1111/cmi.13033
|View full text |Cite
|
Sign up to set email alerts
|

Cholix toxin, an eukaryotic elongation factor 2 ADP‐ribosyltransferase, interacts with Prohibitins and induces apoptosis with mitochondrial dysfunction in human hepatocytes

Abstract: Vibrio cholerae produced-Cholix toxin (Cholix) is a cytotoxin that ADP-ribosylates eukaryotic elongation factor 2, inhibiting protein synthesis, and inducing apoptosis.Here, we identified prohibitin (PHB) 1 and 2 as novel Cholix-interacting membrane proteins in immortalised human hepatocytes and HepG2 cells by Cholix immunoprecipitation assays. The expression level of PHB1 was decreased by Cholix after a 12hr incubation. Cholix-induced poly (ADP-ribose) polymerase (PARP) cleavage was significantly enhanced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…The suppression of Cholix-induced cell death by LRP1 knockdown was only partial. We also reported that Cholix-induced apoptosis was not suppressed at all by LRP1 knockdown in human hepatocytes [46]. Further, Cholix induced significant cell death in human colon cell line HCT116 cells, whose LRP1 gene was mutated by frameshifts [47,48].…”
Section: Cholix Receptormentioning
confidence: 79%
See 1 more Smart Citation
“…The suppression of Cholix-induced cell death by LRP1 knockdown was only partial. We also reported that Cholix-induced apoptosis was not suppressed at all by LRP1 knockdown in human hepatocytes [46]. Further, Cholix induced significant cell death in human colon cell line HCT116 cells, whose LRP1 gene was mutated by frameshifts [47,48].…”
Section: Cholix Receptormentioning
confidence: 79%
“…Cholix-induced eEF2-ADP-ribosylation inhibits ribosomal protein synthesis, resulting in the death of host cells. In addition, by immunoblotting using an anti-Cholix antibody, we found that Cholix was detected in the mitochondrial fraction rather than in the cytosolic compartment, suggesting that Cholix can be translocated into mitochondria; however, there is no information on the translocation mechanism [46].…”
Section: Adp-ribosylation Of Eef2 By Cholixmentioning
confidence: 82%
“…Though lipoprotein receptor-related protein has been shown to bind with Chx, the specific receptor for cholix bining is not known, as the sensitivity of human cell lines to cholix is variable. Recently, prohibitin (PHB) was identified acts as a Chx-binding protein (Yahiro et al, 2019 ), which is expressed by some cell membranes, and also by mitochondria and nucleus. V. cholerae ChxA has some homology with exotoxin A (ToxA) of Pseudomonas aeruginosa , but there is no evidence for lateral transfer (Purdy et al, 2010 ).…”
Section: Major Toxins Produced By V Cholerae and mentioning
confidence: 99%
“…79,81 mARTs serve as a common mechanism for several prokaryotic toxins. 82 ADP-ribosylation of an arginine residue on a membrane-bound GTP-binding protein by cholera toxin or E. coli heat-labile enterotoxin increases the activity of adenylyl cyclase resulting in intestinal fluid and electrolyte flux leading to severe fluid loss and dehydration. 83,84 Both diphtheria toxin and pseudomonas toxin ADP-ribosylate a modified histidine residue in eukaryotic elongation factor 2, which leads to cell death through the inhibition of protein synthesis.…”
Section: Nad Functions As Substratementioning
confidence: 99%